If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 2 = -2x + -1x Reorder the terms: 2 + -1x = -2x + -1x Combine like terms: -2x + -1x = -3x 2 + -1x = -3x Solving 2 + -1x = -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 2 + -1x + 3x = -3x + 3x Combine like terms: -1x + 3x = 2x 2 + 2x = -3x + 3x Combine like terms: -3x + 3x = 0 2 + 2x = 0 Add '-2' to each side of the equation. 2 + -2 + 2x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = 0 + -2 2x = 0 + -2 Combine like terms: 0 + -2 = -2 2x = -2 Divide each side by '2'. x = -1 Simplifying x = -1
| 2(3x-5)=-29 | | 6v^3+12v^2-48v=0 | | 8.95+0.10x=0+0.06x | | -y+6-3y=y+2 | | 2x-5=-x+13 | | -17+62=-5(x+4) | | -8(-8x)-6=-22 | | -3(8-4p)=-15+3p | | 2n+4+6=18 | | x-2(x+1)=3x-10 | | -0.6(r+2)=1.8 | | 110+6x=119+5x | | 2x^2-2x+1=16 | | 5(3x-4)=7+2x | | -15x+9y=0 | | 3(0)=2x+3 | | 6(5x-4)+9=-2(2x+8)-30x | | 7-3x^2=0 | | 720-45x=180 | | -2x+6+5=11 | | -6(x+5)=-30+x | | 0=1+6x+y | | x-(.35x)=375000 | | 3x-4y=93 | | 5r(2)-5=562 | | 180+45x=-720 | | 3x-4y=97 | | 4n-57=165 | | 58=3y-2x | | -15x^2+105x+10=190 | | 5x+7y=60 | | -4x+5x+2=x+2 |